Assessment of Risk Factor for Developing Acute Kidney Injury in the Setting of Acute ST Elevation Myocardial Infarction - Shawqi Watheq Mohammed Ali1 , Fareed Murad Kareem2 , Yihia Mousa Al-Sunbly3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: An acute kidney injury (AKI) is a recognized complication in patients with ST elevation myocardial infarction (STEMI) by several mechanisms and it adversely affects morbidity and mortality on long-term bases (1, 2, and 3). Few studies have investigated which patients with STEMI are at risk of developing AKI (6), and this study is aiming to do this assessment. Patients and Methods: We enrolled patients with STEMI who were admitted to the CCU. KDIGO definitions was utilized to search for development of AKI in these patients throughout their stay in the CCU (their baseline serum creatinine was measured and traced daily thereafter; and their urine output was monitored). Common epidemiological and some relevant medical parameters were recorded for all patients. Results and conclusion: low baseline systolic blood pressure, ejection fraction % and estimated glomerular filtration rate (eGFR); in addition to use of diuretics; are the major risk factors for the development of AKI in the setting of STEMI.